Optimal fiscal policy with utility-enhancing government spending, consumption taxation and a common income tax rate: the case of Bulgaria - Aleksandar Vasilev (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper explores the effects of fiscal policy in an economy based on indirect taxes, and taxing all income at the same rate. The focus of the paper is on the relative importance of consumption vs. income taxation, as well as on the provision of valuable public services. To this end, a Real-Business-Cycle model, calibrated to Bulgarian data (1999-2014), was set up with a richer public finance side. Bulgarian economy was chosen as a case study due to its dependence on consumption taxation as a source of tax revenue. To illustrate the effects of fiscal policy, two regimes were compared and contrasted to one another - exogenous vs. optimal (Ramsey) policy case. The main findings from the computational experiments performed are: (i) The optimal steady-state (capital and labor income) tax rate is zero, as it is the most distortionary tax to use; (ii) The benevolent Ramsey planner provides the optimal amount of the utility-enhancing public services. (iii) The optimal steady-state consumption tax has to triple to finance the optimal level of government spending.
Keywords: D58; 330; consumption tax; income tax; general equilibrium; fiscal policy